Clinical and epidemiological characteristics and impact of non-pharmacological measures on the evolution of the COVID-19 pandemic among residents of a highaltitude region of Peru - Saavedra Córdova , Luisser Dainner (2023)
Objective: To describe the clinical and epidemiological characteristics and the impact of non-pharmacological measures (NFMs) on the evolution of the COVID-19 pandemic among residents of a high-altitude region of Peru.Materials and methods: The study was conducted in the district of Lircay (3,278 m a.s.l.), province of Angaraes, department of Huancavelica, between March 31, 2020, and January 31, 2021 (lockdown period). The Information Technology Department at Hospital Lircay MINSA II-1 provided all COVID-19 patient records used during the aforementioned period of time. The clinical and epidemiological characteristics and the impact of NFMs were evaluated by determining the transmissibility of the virus using the effective reproduction number (Rt). Results: A total of 1,404 COVID-19 patients from the district of Lircay, who were treated at Hospital Lircay MINSA II-1, were studied. The median age was 33 years (IQR: 24.0–45.0); 10.7 % were older adults and 70 % reported no comorbidities at diagnosis. Out of all participants, 2.16 % had a moderate or severe condition, being more frequent in males (p < 0.001). Moreover, the significantly associated comorbidities were obesity (p < 0.001) and hypertension (p = 0.004). The average case fatality rate was 0.9 %; however, in moderate–severe cases, it reached 26.7 % (p < 0.001), and the elderly population was the most affected one. The lockdown, understood as an NFM, generated an Rt of 2.98 (95 % CI: 1.54–5.14) in July, and the end of the lockdown plus the economic recovery generated an Rt of 9.94 (95 % CI: 4.19–19.45) in December. After Christmas, focused lockdown was introduced and, 14 days later, an Rt reduction of up to 0.79 (95 % CI: 0.41–1.36) was observed. Conclusions: In this high-altitude region, the COVID-19 overall case fatality rate was low; this could be related to the characteristics of the population (young age and low prevalence of comorbidities). Lockdown apparently proved to be an effective measure for controlling SARS-CoV-2 transmissibility